Sovereign credit risk spillover - Xie, Hui (2014)
This thesis examines cross-market correlations between means and variances in sovereign credit markets and captures the presence of any contagion effect by focusing on parallel movements between markets in the wake of the recent crisis. Furthermore, it focuses on the effect of policy interventions on the dynamics of these correlations.